Pengaruh Motivasi Kerja dan Budaya Organisasi Terhadap Kinerja Karyawan Dinas Pendidikan Kabupaten Kepulauan Sula The Effect of Work Motivation And Organizational Culture on Employees Performance in Dinas Pendidikan, Sula Islands - Ida Sriyanti Ratna Sungkono; Marwan Marwan; Milwan Milwan (EBBANK, 2020)
The purpose of this study was to analyze the influence of motivation and organizational culture on the performance of the employees of the Sula Islands District Education Office. This research was conducted on employees of the Sula Islands District Education Office with a population of 108 employees. Using the incidental sampling technique, the number of samples used was 85 respondents, using the explanatory research method. While the theory used is Maslow's motivation theory. The research instrument used was a questionnaire. The independent variabels in this study are work motivation and organizational culture, while the dependent variabel is employee performance. Measurement of variabels is carried out using a Likert scale. Data analysis was performed using multiple linear regression analysis method. The results of this study indicate that there is a partial positive influence between work motivation and organizational culture on employee performance. Work motivation and organizational culture simultaneously have a significant effect on employee performance. The results of the analysis show that 24.4% of changes in employee performance variabels are influenced by work motivation and organizational culture.